COMPARATIVE STUDY OF THE EFFECTS OF A-PRF VERSUS GTR IN THE TREATMENT OF COMBINED ENDO PERIODONTAL LESIONS - Ada Stefanescu; Irina-Georgeta Șufaru; Norina Consuela Forna; Fabian Cezar Lupu; Doriana Agop-Forna; Kamel Earar (Romanian Society of Oral Rehabilitation, 2024)
In the present study we aimed to investigate the effects of therapy of combined endo -periodontal lesions in patients who underwent surgical treatment with debridement flap plus resorbable membrane placement (GTR) and debridement flap plus platelet enriched fibrin (A-PRF) on periodontal clinical and radiologic parameters. The study aims to investigate the specific effects on mandibular premolar teeth affected by combined endo-periodontal lesions. An important contribution has been made to the understanding of how these therapeutic procedures influence the course and outcome of endo periodontal lesions. To date, according to the information identified in the literature, this is the first study to evaluate these effects on mandibular premolar teeth with true endo periodontal combined lesions. This research has the potential to provide essential information on the optimal ways to treat this type of lesion. By evaluating and comparing the efficacy of two distinct therapeutic protocols, we aimed to identify the most effective and promising strategies for the management of these delicate clinical conditions. We opted for unit tooth selection to remove the risk of factors compromising the clarity of the results, such as furcation lesions at the level of pluri-radicular teeth or variations related to anatomo-physiological particularities in different areas of the maxilla.